COMPARISON OF INTRAVENOUS LIGNOCAINE, TRAMADOL, AND KETOROLAC FOR ATTENUATION OF PROPOFOL INJECTION PAIN - RANI, HANUMANLA BABY; POOJA, SRI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: This study aims to study and compare the efficacy of lignocaine, tramadol, and ketorolac in minimizing propofol injection pain. Methods: This is a randomized control research that was conducted on 100 patients between the ages of 18 and 60 years at the department of anesthesiology and critical care. Being planned for elective surgery under general anesthesia with propofol as an inducing drug, with an ASA grade I or II body mass index of 19–30 kg/m2. Each of the four groups of 25 patients was randomly selected from among all the patients. Results: The incidence of pain was 20% in the lignocaine group and 28% in the groups treated with tramadol and ketorolac. 92% of patients in the normal saline group felt discomfort during the propofol injection. In comparison to group N (7.46±2.78), the mean pain score in groups L (0.80±1.32), T (0.98±1.70), and K (1.49±1.55) was statistically significant (p<0.0001). Group N saw noticeably less side effects than the other groups. Statistics showed that groups L, T, and K were comparable. Conclusion: We recommend the use of these agents as pre-treatment to propofol to increase the patient acceptability of this ideal anesthetic agent.